2019
DOI: 10.4028/www.scientific.net/ssp.296.209
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Verification of Properties of Alkali-Activated Composite

Abstract: The paper deals to create alkali activated composite based on the recipe of high-strength concrete. The paper includes the review of conditions for high-strength concrete proposing and preparation. Principles of design of high performance concrete based on Portland cement as a binder were described. The experiment was focused on the strength investigation of composites with different ratios of cement to slag, and also the effect of used activator on strength parameters was investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Therefore, the research work of the team included efforts to use a solid activator in the form of sodium metasilicate. This material has a silicate modulus value of 1, and, so, in terms of workability [31,32], it is an ideal activator because, as previous research has shown, the optimal value of silicate modulus is in the range of 1-2; the increasing value significantly decreases workability time [29,30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the research work of the team included efforts to use a solid activator in the form of sodium metasilicate. This material has a silicate modulus value of 1, and, so, in terms of workability [31,32], it is an ideal activator because, as previous research has shown, the optimal value of silicate modulus is in the range of 1-2; the increasing value significantly decreases workability time [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…As a basic mixture, the previously verified and tested mixture from the previous work was used [9,[28][29][30]. The basic mixture was derived from initial experiments, where the strength properties were monitored with different replacements of BFS with fly ash and CBPD, with the possibility of using different activators.…”
Section: Mixture Preparationmentioning
confidence: 99%
“…As a reference mixture, previously verified mixtures tested in the previous works [38][39][40][41] were used in the experimental part. The basic mixture was derived from initial experiments, where the strength properties were monitored with different replacement of BFS with fly ash and CBPD with the possibility of using different activators.…”
Section: Mixturesmentioning
confidence: 99%
“…[8] Mixture. As a reference mixture in the experimental part were used previously verified formulas, which were tested in the in previous works [11,12,13,14]. For REC 1, the amount of activator is calculated over the whole binder amount.…”
mentioning
confidence: 99%